Aspek Hukum Pengawasan pada Perbankan Syariah di Indonesia - Bagya Agung Prabowo (Fakultas Hukum Universitas Islam Indonesia, 2003)
Islamic Banking can only developed if investor and customers prefer to use Islamic Banks over conventional bank. The Islamic Banks are required to consider the interests of both investor and customers, as well as the need to maintains their trust In order to promote the Islamic Banking credibility; the Islamic Banking needs a direct control from the Bl (Bank Indonesia) and the DPS (Dewan Pengawas Syariah). This mechanism is very important In one hand Bl as control bank in Indonesia can maintain and control CAR (Capita Adequate Ratio) on theother hand, the DPS has as authority to control subtansial aspects of syariah.